Risk factors for the recurrence of obstetrical anal sphincter injury and the role of a mediolateral episiotomy: an analysis of a national registry. (30th April 2020) - van Bavel, J; Ravelli, ACJ; Abu‐Hanna, A; Roovers, JPWR; Mol, BW; de Leeuw, JW
Abstract : Objective: The assessment of risk factors, including mediolateral episiotomy (MLE), for the recurrence of obstetric anal sphincter injury (rOASI). Design: Population‐based cohort study. Setting: Data from the nationwide database of the Dutch Perinatal Registry (Perined). Population: A cohort of 391 026 women at term, of whom 9943 had an OASI in their first delivery and had a second vaginal delivery of a liveborn infant in cephalic position. Methods: Possible risk factors were tested for statistical significance using univariate and multivariate logistic regression analysis. Main outcome measures: Rate of rOASI. Results: The rate of rOASI was 5.8%. Multivariate analysis identified a birthweight of ≥4000 g (adjusted OR, aOR, 2.1, 95% CI 1.6–2.6) and a duration of second stage of ≥30 minutes (aOR 1.8, 95% CI 1.4–2.3) as statistically significant risk factors for rOASI. Mediolateral episiotomy was associated with a statistically significant lower rate of rOASI in spontaneous vaginal delivery (SVD) (aOR 0.4, 95% CI 0.3–0.5) and in operative vaginal delivery (OVD) (aOR 0.2, 95% CI 0.1–0.5). Conclusions: Women with a history of OASI have a higher rate of OASI in their next delivery. Duration of the second stage of ≥30 minutes and a birthweight of ≥4000 g are significantly associated with an increased rate of rOASI. Mediolateral episiotomy is associated with a significantly lower rate of rOASI in both SVD and OVD. Tweetable abstract: Mediolateral episiotomy is associated with a significant lower recurrence rate of OASI in women with an OASI in their first delivery. Tweetable abstract: Mediolateral episiotomy is associated with a significant lower recurrence rate of OASI in women with an OASI in their first delivery.